2016
DOI: 10.1111/1751-2980.12404
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Helicobacter pylori‐related chronic gastritis, gastric adenoma and early gastric cancer by magnifying endoscopy

Abstract: Evaluating the prevalence and severity of gastritis by endoscopy is useful for estimating the risk of gastric cancer (GC). Moreover, understanding the endoscopic appearances of gastritis is important for diagnosing GC due to the fact that superficial mucosal lesions mimicing gastritis (gastritis-like lesions) are quite difficult to be detected even with optimum preparation and the best technique, and in such cases tissue biopsy is often not very accurate for the diagnosis of gastric epithelial neoplasia. Magni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…In this study, FBN1 gene expression was first detected and showed a gradually increasing trend in normal gastric mucosa, chronic superficial gastritis, chronic atrophic gastritis, and gastric cancer tissues and showed strong expression in gastric cancer tissues. Chronic superficial gastritis and chronic atrophic gastritis are precancerous lesions of gastric cancer (16,17). The results suggested that FBN1 can be used as a marker to determine precancerous lesions of gastric cancer, which may be closely related to the progression of gastric cancer and the prognosis of patients.…”
Section: Discussionmentioning
confidence: 94%
“…In this study, FBN1 gene expression was first detected and showed a gradually increasing trend in normal gastric mucosa, chronic superficial gastritis, chronic atrophic gastritis, and gastric cancer tissues and showed strong expression in gastric cancer tissues. Chronic superficial gastritis and chronic atrophic gastritis are precancerous lesions of gastric cancer (16,17). The results suggested that FBN1 can be used as a marker to determine precancerous lesions of gastric cancer, which may be closely related to the progression of gastric cancer and the prognosis of patients.…”
Section: Discussionmentioning
confidence: 94%